A hot-bent integrated rock plate basin that prevents cracking
By adding toughening agent to the blank of the ceramic rock slab, the problem of the ceramic rock slab prone to cracking during hot bending is solved, and the effect of improving toughness and mechanical properties is achieved.
Patent Information
- Application Number
- CN202411274703.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Ceramic rock slabs are prone to cracking during thermal bending, resulting in greater brittleness and need to improve their toughness to reduce the occurrence of cracking.
The toughening agent is added to the blank of the ceramic rock slab. The toughening agent uses the spherical structure of the alumina to separate the carbon nanotubes from the carbon nanotubes to avoid their agglomeration, thereby Form a dense body structure.
It effectively prevents the cracking of ceramic rock slabs during hot bending, and significantly improves the toughness and mechanical properties of the washbasin.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ceramic technology, and in particular to a hot-bent integrated rock slab basin that prevents cracking. Background Art
[0002] Ice crack is actually a phenomenon of oblique crack. It is characterized by white crack edges of different lightness and shade in the glaze layer, forming a rose petal-like pattern, which is distributed layer by layer, thus creating an antique, ice-like and jade-like artistic beauty. Applying cracks to ceramic products will bring a unique artistic flavor to the products, thereby increasing the competitiveness of the products.
[0003] The hot-bent one-piece rock basin is made by processing the ceramic rock slab. When the rock slab reaches the softening point, it softens and deforms to obtain a curved surface, which is then prepared through mold processing. This one-piece molding technology is not only faster to prepare, but also the prepared basin has no splicing and is easy to maintain. In addition, its acid and alkali corrosion resistance, stain resistance, and weather resistance are superior to natural stone basins. Coupled with its unique decorative effect, it is currently very popular.
[0004] CN114853342B provides a hot-bending bright ceramic rock plate and a preparation method thereof, wherein the hot-bending bright ceramic rock plate comprises a transparent polishing glaze suitable for the hot-bending process, and the chemical composition of the transparent polishing glaze comprises CaO, ZnO, SiO 2 and Al 2 O 3 , of which the mass percentage of CaO is 8%-9%, the mass percentage of ZnO is 6%-8%, and the mass percentage of SiO 2 and Al 2 O 3 The mass ratio is (5-8): 1. The hot-bending bright ceramic rock plate prepared by the transparent polishing glaze formula and preparation method of the invention has high gloss and transparency, and stable color. After the product is processed by the hot bending process, the glaze surface of the product can maintain a high gloss (generally > 80°), and the color of the ceramic rock plate product is not much different from that before hot bending, and can be well matched with the original design color.
[0005] CN115849888B discloses a high-strength and high-toughness ceramic rock plate and its preparation method. The high-strength and high-toughness ceramic rock plate includes a green body, a base glaze layer, a decorative layer and a surface glaze layer stacked in sequence; wherein, by weight, the raw materials forming the green body include: 20-40 parts of potassium feldspar, 10-20 parts of sodium feldspar, 25-40 parts of Suzhou soil, 10-20 parts of quartz sand, 3-16 parts of α-alumina, and 0-7 parts of zirconium powder. The raw materials of the green body of the invention cooperate with each other to form mullite, quartz and corundum. These crystal phase structures grow in an interlaced manner and are evenly distributed in the matrix, together forming the skeleton of the matrix; at the same time, Al 2O 3 、SiO 2 The equal grains are evenly interspersed in the mullite network, which significantly improves the flexural strength of the ceramic rock plate; and the body layer and glaze layer of the invention are tightly combined, and through the synergistic effect of the two, the fracture toughness of the ceramic rock plate is significantly improved.
[0006] The main problem with ceramic rock slabs today is that they are very brittle and may crack when subjected to hot bending. Therefore, their toughness needs to be improved to reduce the occurrence of this phenomenon. Summary of the invention
[0007] In view of the above-mentioned defects in the prior art, the technical problem to be solved by the present invention is to provide a hot-bent one-piece rock slab basin that prevents cracking and a preparation method thereof.
[0008] Carbon nanotubes (CNTs) are widely used as a tubular material with excellent mechanical, physical and high temperature resistance properties. When added to ceramics, most of the CNTs are located at the grain boundaries. When the outer layer breaks, the internal CNTs are "pulled out" to prevent further fractures. They can also serve as crack bridging components and form a CNTs network inside, thereby enhancing the toughening effect. However, carbon nanotubes still have defects. Their own structure makes them very easy to agglomerate, resulting in layered stacking. Once agglomeration occurs, it will form a phenomenon of uneven components inside when mixed with other components. This will not only not bring toughening effects to ceramics, but will cause uneven stress and thus have the opposite effect. Therefore, the present invention provides a toughening agent, which is a composite of carbon nanotubes and zirconium and then coated on the surface of alumina under the action of a dispersant. Due to the spherical structure of alumina, the carbon nanotubes are cleverly separated and are not easy to agglomerate. The addition of zirconium and alumina can make the sintered green body more dense, thereby further improving the mechanical properties of the rock plate. Alumina sol not only acts as a medium to mix the components, but also acts as a filler, making the toughening and densification effects of the final toughening agent better. After the toughening agent is added to the blank, it can prevent the basin from cracking during hot bending and improve the toughness of the final prepared basin.
[0009] To achieve the above-mentioned purpose, the present invention provides a hot-bent integrated rock slab basin that prevents cracking, comprising a body layer and a glaze layer; the body layer comprises the following raw materials in parts by weight: 20-30 parts of potassium feldspar, 15-20 parts of sodium feldspar, 10-20 parts of limestone, 5-10 parts of quartz sand, 3-5 parts of fluorite, 3-5 parts of talc, and 1-3 parts of toughening agent; the glaze layer comprises the following raw materials in parts by weight: 50-60 parts of potassium feldspar, 10-15 parts of kaolin, 10-15 parts of limestone, 12-17 parts of pearl powder, 0.1-1 parts of pigment, and 0.1-0.5 parts of sodium tripolyphosphate.
[0010] Furthermore, the pigment is any one of titanium dioxide, copper oxide, and vanadium zirconium blue.
[0011] The preparation method of the toughening agent comprises the following steps:
[0012] Add carbon nanotubes and zirconium powder to alumina sol, stir and mix evenly, add 0.5 mol / L dilute hydrochloric acid to adjust the pH to 5-6, then add dispersant, continue stirring for 0.5-1h, then add alumina, stir for 1-2h and dry to obtain the toughening agent.
[0013] Furthermore, the dispersant is Pluronic® F-127.
[0014] Furthermore, the drying is carried out at 70-80° C. for 40-50 hours.
[0015] Preferably, the preparation method of the toughening agent comprises the following steps:
[0016] Add 0.2-1 parts by weight of carbon nanotubes and 0.5-2.5 parts by weight of zirconium powder to 100-300 parts by weight of alumina sol, stir and mix evenly, add 0.5 mol / L dilute hydrochloric acid to adjust the pH to 5-6, then add 1-5 parts by weight of dispersant, continue stirring for 0.5-1h, then add 30-40 parts by weight of alumina, stir for 1-2h, and dry at 70-80°C for 40-50h to obtain the toughening agent.
[0017] A method for preparing a hot-bent integrated rock plate basin that prevents cracking comprises the following steps:
[0018] S1. Weigh and mix the raw materials according to the formula of the green body layer, and sinter to obtain the green body layer;
[0019] S2. Weigh and mix the raw materials according to the glaze formula requirements, and ball mill for 20-40 hours;
[0020] S3, cutting the blank into corresponding sizes, heating it and putting it into a mold, cooling and solidifying it after hot bending, and drilling holes to obtain a basin;
[0021] S4. Glaze the surface of the basin and then fire it in a kiln.
[0022] Furthermore, in step S1, the sintering temperature is 1050-1150° C., and the sintering time is 1-2 hours.
[0023] Furthermore, in step S2, the mass ratio of glaze: zirconium oxide balls: water is 1:2:0.5-1.
[0024] Furthermore, the temperature of the hot bending treatment is 1200-1300°C.
[0025] Furthermore, the firing in step S5 includes heating the kiln temperature to 500-600°C at 5°C / min, continuing to heat the kiln to 900-1000°C, keeping the temperature for 1-2 hours, and then continuing to heat the kiln to 1200-1300°C and keeping the temperature for 1-2 hours before naturally cooling to room temperature.
[0026] Preferably, the method for preparing the hot-bent integrated rock slab basin that prevents cracking comprises the following steps:
[0027] S1. Weigh and mix the raw materials according to the formula of the green body layer, and sinter at 1050-1150°C for 1-2h to obtain the green body layer;
[0028] S2. Weigh and mix the raw materials according to the glaze formula requirements to obtain the glaze, and then ball-mill the glaze, wherein the mass ratio of glaze: zirconium oxide ball: water is 1:2:0.5-1, and the ball-milling is performed for 20-40 hours;
[0029] S3, cutting the green body layer into corresponding sizes, heating it and putting it into a mold, subjecting it to a hot bending treatment at 1200-1300°C, cooling and solidifying it, and drilling a hole to obtain a basin;
[0030] S4. Glaze the surface of the basin with the glaze in step S2, and then load the basin into a kiln for firing. The firing process includes heating the basin at a rate of 5°C / min to a kiln temperature of 500-600°C, then heating the basin to 900-1000°C, keeping the temperature for 1-2 hours, then heating the basin to 1200-1300°C, keeping the temperature for 1-2 hours, and then naturally cooling the basin to room temperature.
[0031] Beneficial effects of the present invention:
[0032] The present invention can prevent the basin from cracking during hot bending by adding a toughening agent to the blank, and improve the toughness of the finally prepared basin. The glaze prepared by the present invention can form unique cracks after firing, so the prepared basin has the advantages of unique style, good toughness, simple preparation, etc. DETAILED DESCRIPTION
[0033] Zirconium powder, item number: yj896548, Beijing Yijin New Materials.
[0034] Alumina, spherical, particle size: 30μm, model: ML-Al 2 O 3 -W30, Zhejiang Manli Nanotechnology.
[0035] Alumina sol, pH=11, solid content 10wt%.
[0036] Pluronic® F-127, Beishi Zongheng Science. Example 1
[0037] A method for preparing a hot-bent integrated rock plate basin that prevents cracking comprises the following steps:
[0038] S1. Mix 25 parts of potassium feldspar, 15 parts of sodium feldspar, 15 parts of limestone, 8 parts of quartz sand, 4 parts of fluorite, 5 parts of talc and 2 parts of toughening agent by weight, and sinter at 1100°C for 2h to obtain a green body layer;
[0039] S2, by weight, 55 parts of potassium feldspar, 12 parts of kaolin, 10 parts of limestone, 15 parts of pearl powder, 0.5 parts of titanium dioxide, and 0.3 parts of sodium tripolyphosphate were mixed to obtain a glaze, and the glaze: zirconium oxide ball: water mass ratio was 1:2:0.8, and the ball milling was performed for 30 hours;
[0040] S3, cutting the green body layer into corresponding sizes, heating it and putting it into a mold, subjecting it to a hot bending treatment at 1250°C, cooling and solidifying it, and drilling a hole to obtain a basin;
[0041] S4. Glaze the surface of the basin with the glaze in step S2, and then load the basin into a kiln for firing. The firing process includes heating the basin at a rate of 5°C / min until the kiln temperature reaches 600°C, then heating the basin to 950°C, keeping the temperature for 2 hours, then heating the basin to 1300°C, keeping the temperature for 2 hours, and then naturally cooling the basin to room temperature.
[0042] The preparation method of the toughening agent comprises the following steps:
[0043] 1 g of carbon nanotubes and 2.4 g of zirconium powder were added to 200 g of alumina sol, and after stirring and mixing evenly, 0.5 mol / L of dilute hydrochloric acid was added to adjust the pH to 5, and then 3 g of Pluronic® F-127 was added. After continuing to stir for 1 hour, 34.5 g of alumina was added. After stirring for 2 hours, the mixture was dried at 80°C for 48 hours to obtain the toughening agent. Example 2
[0044] The same as Example 1, the only difference is that the weight portion of the toughening agent is 1 part. Example 3
[0045] The same as Example 1, the only difference is that the weight portion of the toughening agent is 3 parts.
[0046] Comparative Example 1
[0047] A method for preparing a hot-bent integrated rock plate basin that prevents cracking comprises the following steps:
[0048] S1. Mix 25 parts of potassium feldspar, 15 parts of sodium feldspar, 15 parts of limestone, 8 parts of quartz sand, 4 parts of fluorite, 5 parts of talc and 2 parts of carbon nanotubes by weight, and sinter at 1100° C. for 2 h to obtain a green body layer;
[0049] S2, by weight, 55 parts of potassium feldspar, 12 parts of kaolin, 10 parts of limestone, 15 parts of pearl powder, 0.5 parts of titanium dioxide, and 0.3 parts of sodium tripolyphosphate were mixed to obtain a glaze, and the glaze: zirconium oxide ball: water mass ratio was 1:2:0.8, and the ball milling was performed for 30 hours;
[0050] S3, cutting the green body layer into corresponding sizes, heating it and putting it into a mold, subjecting it to a hot bending treatment at 1250°C, cooling and solidifying it, and drilling a hole to obtain a basin;
[0051] S4. Glaze the surface of the basin, then load it into the kiln for firing. The firing process includes heating the basin at a rate of 5°C / min to a temperature of 600°C, then heating it to 950°C, keeping it at that temperature for 2 hours, then heating it to 1300°C and keeping it at that temperature for 2 hours, then naturally cooling it to room temperature.
[0052] Comparative Example 2
[0053] A method for preparing a hot-bent integrated rock plate basin that prevents cracking comprises the following steps:
[0054] S1. Mix 25 parts of potassium feldspar, 15 parts of sodium feldspar, 15 parts of limestone, 8 parts of quartz sand, 4 parts of fluorite, 5 parts of talc and 2 parts of zirconium powder by weight, and sinter at 1100°C for 2h to obtain a green body layer;
[0055] S2, by weight, 55 parts of potassium feldspar, 12 parts of kaolin, 10 parts of limestone, 15 parts of pearl powder, 0.5 parts of titanium dioxide, and 0.3 parts of sodium tripolyphosphate were mixed to obtain a glaze, and the glaze: zirconium oxide ball: water mass ratio was 1:2:0.8, and the ball milling was performed for 30 hours;
[0056] S3, cutting the green body layer into corresponding sizes, heating it and putting it into a mold, subjecting it to a hot bending treatment at 1250°C, cooling and solidifying it, and drilling a hole to obtain a basin;
[0057] S4. Glaze the surface of the basin with the glaze in step S2, and then load the basin into a kiln for firing. The firing process includes heating the basin at a rate of 5°C / min until the kiln temperature reaches 600°C, then heating the basin to 950°C, keeping the temperature for 2 hours, then heating the basin to 1300°C, keeping the temperature for 2 hours, and then naturally cooling the basin to room temperature.
[0058] Comparative Example 3
[0059] A method for preparing a hot-bent integrated rock plate basin that prevents cracking comprises the following steps:
[0060] S1. Mix 25 parts of potassium feldspar, 15 parts of sodium feldspar, 15 parts of limestone, 8 parts of quartz sand, 4 parts of fluorite, 5 parts of talc and 2 parts of alumina by weight, and sinter at 1100° C. for 2 h to obtain a green body layer;
[0061] S2, by weight, 55 parts of potassium feldspar, 12 parts of kaolin, 10 parts of limestone, 15 parts of pearl powder, 0.5 parts of titanium dioxide, and 0.3 parts of sodium tripolyphosphate were mixed to obtain a glaze, and the glaze: zirconium oxide ball: water mass ratio was 1:2:0.8, and the ball milling was performed for 30 hours;
[0062] S3, cutting the green body layer into corresponding sizes, heating it and putting it into a mold, subjecting it to a hot bending treatment at 1250°C, cooling and solidifying it, and drilling a hole to obtain a basin;
[0063] S4. Glaze the surface of the basin with the glaze in step S2, and then load the basin into a kiln for firing. The firing process includes heating the basin at a rate of 5°C / min until the kiln temperature reaches 600°C, then heating the basin to 950°C, keeping the temperature for 2 hours, then heating the basin to 1300°C, keeping the temperature for 2 hours, and then naturally cooling the basin to room temperature.
[0064] Comparative Example 4
[0065] A method for preparing a hot-bent integrated rock plate basin that prevents cracking comprises the following steps:
[0066] S1. Mix 25 parts of potassium feldspar, 15 parts of sodium feldspar, 15 parts of limestone, 8 parts of quartz sand, 4 parts of fluorite and 5 parts of talc by weight, and sinter at 1100° C. for 2 h to obtain a green body layer;
[0067] S2, by weight, 55 parts of potassium feldspar, 12 parts of kaolin, 10 parts of limestone, 15 parts of pearl powder, 0.5 parts of titanium dioxide, and 0.3 parts of sodium tripolyphosphate were mixed to obtain a glaze, and the glaze: zirconium oxide ball: water mass ratio was 1:2:0.8, and the ball milling was performed for 30 hours;
[0068] S3, cutting the green body layer into corresponding sizes, heating it and putting it into a mold, subjecting it to a hot bending treatment at 1250°C, cooling and solidifying it, and drilling a hole to obtain a basin;
[0069] S4. Glaze the surface of the basin with the glaze in step S2, and then load the basin into a kiln for firing. The firing process includes heating the basin at a rate of 5°C / min until the kiln temperature reaches 600°C, then heating the basin to 950°C, keeping the temperature for 2 hours, then heating the basin to 1300°C, keeping the temperature for 2 hours, and then naturally cooling the basin to room temperature.
[0070] Test Example 1
[0071] The mechanical properties of the rock slab basins prepared in the embodiment and the control example were tested by three-point flexure method and indentation method. The test results are shown in Table 1.
[0072] Table 1 Mechanical properties test results of hot-bent integrated rock plate basin to prevent cracking
[0073]
[0074] By comparing the control example 4 with the embodiment, it can be found that adding a toughening agent to the blank can significantly improve the flexural strength of the basin, which shows that the toughening agent has a good effect of improving toughness and improves the defect of large ceramic brittleness. Compared with the control examples 1 to 3, the embodiment uses a toughening agent prepared by carbon nanotubes, zirconium powder and alumina as raw materials. After the carbon nanotubes and zirconium are compounded, they are coated on the surface of alumina under the action of a dispersant. The spherical structure of alumina makes the carbon nanotubes cleverly separated and not easy to agglomerate, and the addition of zirconium and alumina can make the sintered blank more compact, thereby further improving the mechanical properties of the rock plate. Among them, the alumina sol not only acts as a medium to allow the components to be mixed, but also acts as a filler, so that the toughening and densification effects of the toughening agent finally formed are better. Therefore, compared with other single components as toughening agent Example 1, the toughening effect is significantly better. When the toughening agent is added to the blank, it can not only prevent the basin from cracking during hot bending, but also improve the toughness of the basin finally prepared. Compared with Examples 2 and 3, the flexural strength of Example 1 increases first and then decreases as the amount of toughening agent increases, which indicates that excessive addition of toughening agent may lead to a decrease in performance. Therefore, the addition amount in Example 1 is optimal.
[0075] Test Example 2
[0076] The "QXYS-1004-2024 hot-bent rock plate basin" was used to conduct various performance tests on the basin prepared by the present invention and the corresponding assembled floor-standing cabinet. The specific results are shown in Table 2.
[0077] Table 2 Comprehensive performance test results of hot-bent integrated rock slab basin to prevent cracking
[0078]
[0079] From the comprehensive performance test, it can be seen that the integrated basin prepared by the present invention has good drainage, excellent cold and hot stability, resistance to chemical corrosion and stains, stable surface, high countertop strength, safe ingredients, and great market competitiveness.
[0080] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A cracked hot-bent integrated rock plate basin, characterized in that: It comprises a body layer and a glaze layer; the body layer comprises the following raw materials in parts by weight: 20-30 parts of potassium feldspar, 15-20 parts of sodium feldspar, 10-20 parts of limestone, 5-10 parts of quartz sand, 3-5 parts of fluorite, 3-5 parts of talc, and 1-3 parts of toughening agent; the glaze layer comprises the following raw materials in parts by weight: 50-60 parts of potassium feldspar, 10-15 parts of kaolin, 10-15 parts of limestone, 12-17 parts of pearl powder, 0.1-1 parts of pigment, and 0.1-0.5 parts of sodium tripolyphosphate; The preparation method of the toughening agent comprises the following steps: Add 0.2-1 parts by weight of carbon nanotubes and 0.5-2.5 parts by weight of zirconium powder to 100-300 parts by weight of alumina sol, stir and mix evenly, add 0.5 mol / L dilute hydrochloric acid to adjust the pH to 5-6, then add 1-5 parts by weight of dispersant, continue stirring for 0.5-1h, then add 30-40 parts by weight of alumina, stir for 1-2h, and dry at 70-80°C for 40-50h to obtain the toughening agent.
2. The cracked hot-bent integrated rock slab basin according to claim 1, characterized in that: The pigment is any one of titanium dioxide, copper oxide and vanadium zirconium blue.
3. The method for preparing the cracked hot-bent integrated rock plate basin according to any one of claims 1 or 2, characterized in that: The steps include: S1. Weigh and mix the raw materials according to the formula of the green body layer, and sinter at 1050-1150°C for 1-2h to obtain the green body layer; S2. Weigh and mix the raw materials according to the glaze formula requirements to obtain the glaze, and then ball-mill the glaze, wherein the mass ratio of glaze: zirconium oxide ball: water is 1:2:0.5-1, and the ball-milling is performed for 20-40 hours; S3, cutting the green body layer into corresponding sizes, heating it and putting it into a mold, subjecting it to a hot bending treatment at 1200-1300°C, cooling and solidifying it, and drilling a hole to obtain a basin; S4. Glaze the surface of the basin with the glaze in step S2, and then load the basin into a kiln for firing. The firing process includes heating the basin at a rate of 5°C / min to a kiln temperature of 500-600°C, then heating the basin to 900-1000°C, keeping the temperature for 1-2 hours, then heating the basin to 1200-1300°C, keeping the temperature for 1-2 hours, and then naturally cooling the basin to room temperature to obtain a cracked hot-bent integrated basin.
Citation Information
Patent Citations
Carbon nano tube enhanced ceramic tile
CN104193292A
High-curvature wide-color-gamut ceramic curved surface rock plate and preparation method and application thereof
CN113979738A